2014
DOI: 10.1111/bjir.12111
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Union‐Centred Approach: A Critical Evaluation of Recent Trade Union Elections in China

Abstract: Many Western scholars have regarded union democracy and elections as affairs that are internal to trade unions and unconnected with outside forces. Going beyond the mainstream union-centred approach, this study critically assesses one significant type of union election that has been emerging in China since 2010 and that has been driven by different forces from previous elections. Previous workplace union elections had been 'top-down' -initiated by the party-state or its apparatuses, or else transnational corpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 37 publications
2
41
2
Order By: Relevance
“…In general, unions in the private sector have been established via collaboration between management and higher level unions seeking to meet pre-set targets for union density. Potential associational power was further undermined by the widespread practice of appointing rather than electing workplace representatives (Hui and Chan 2015). Trade union elections have been piloted in the provinces of Guangdong and Zhejiang (Pringle 2011;Chan and Hui 2015) but remain very much the exception and are often manipulated by management anyway.…”
Section: Strikesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, unions in the private sector have been established via collaboration between management and higher level unions seeking to meet pre-set targets for union density. Potential associational power was further undermined by the widespread practice of appointing rather than electing workplace representatives (Hui and Chan 2015). Trade union elections have been piloted in the provinces of Guangdong and Zhejiang (Pringle 2011;Chan and Hui 2015) but remain very much the exception and are often manipulated by management anyway.…”
Section: Strikesmentioning
confidence: 99%
“…Interviews conducted after the second strike suggested that the election of a manager as chair reflected workers" concerns regarding access to management policy and data as well as a degree management manipulation also reflected in This is the accepted version of a forthcoming article that will be published by Sage in ILR Review: http://journals.sagepub.com/loi/ilr Accepted version downloaded from SOAS Research Online: http://eprints.soas.ac.uk/24689/ strike-driven elections elsewhere (Chan and Hui 2015). While it is probably too late to verify the degree of manipulation, Cao and Meng nevertheless argue that the election "signalled that grassroots union reform became possible" (2017: 6).…”
Section: Add Figure 1 About Herementioning
confidence: 99%
“…Extant studies have also assessed the implications of the strikes for trade union reforms (e.g. Hui and Chan ; Lüthje ). In particular, it is believed that strikes have led to the democratic election of grassroots union representatives at workplaces, i.e.…”
Section: Strikes In China: Causes Of Industrial Actions and The Role mentioning
confidence: 99%
“…Chang ); reforms in workplace trade union elections as a result of the strike (e.g. Hui and Chan ); and the introduction of collective bargaining regulations at the regional level (e.g. Lüthje ).…”
mentioning
confidence: 99%
“…The fourth measure taken to contain labour unrest is to promote democratic union elections at the plant level. However, some studies have found that these elections are only indirect and quasi-democratic, and are not necessarily able to pacify the aggrieved workers (Hui and Chan 2015).…”
Section: Controlled Class Organisationsmentioning
confidence: 99%